1981
DOI: 10.1037/0021-9010.66.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Nonperformance influences on performance evaluations: A laboratory phenomenon?

Abstract: A number of recent studies have investigated the effects of nonperformance factors (i.e., gender and race) on a variety of organizational criteria, including performance evaluations. It is argued that results from studies of this nature may be attributable to a research design that bears little resemblance to the performance appraisal process in real organizational contexts. Consequently, the present study was designed to examine the effects of two nonperformance factors (ratee race and rater race) and an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

1982
1982
1991
1991

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
1
22
2
Order By: Relevance
“…For example, in this study actual ongoing work behavior was not observed; instead a vignette was read. Although the "paper person" paradigm has been the target of some criticism (Wendelken & Inn, 1981), recent research indicates that such concerns may be overstated. Murphy, Herr, Lockhart, and Maguire ( 1986), for example, conducted a meta-analysis of performance appraisal research that contrasted the effect sizes of "paper people" versus "behavior observation" studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in this study actual ongoing work behavior was not observed; instead a vignette was read. Although the "paper person" paradigm has been the target of some criticism (Wendelken & Inn, 1981), recent research indicates that such concerns may be overstated. Murphy, Herr, Lockhart, and Maguire ( 1986), for example, conducted a meta-analysis of performance appraisal research that contrasted the effect sizes of "paper people" versus "behavior observation" studies.…”
Section: Discussionmentioning
confidence: 99%
“…Critics argue that given the massive differences between laboratory and field settings, it seems unlikely that the results obtained in laboratories will generalize to actual organizations (e.g. Ilgen and Favero, 1985;Wendelken and Inn, 1981).…”
Section: Artificial Experimental Proceduresmentioning
confidence: 99%
“…The value of laboratory experimentation for studying work behaviour has often been debated (e.g. Dipboye and Flanagan, 1979;Landy and Bates, 1973;Wendelken and Inn, 1981). Although the criticisms of the laboratory have been refuted in the past (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all laboratory or field studies found these effects (Cascio & Phillips, 1979); in field studies such as those of Mobley (1982) and Wendelken & Inn (1981), only about 4% of the variance was due to these effects.…”
Section: Rater-ratee Relationshipsmentioning
confidence: 99%
“…Wendelken and Inn (1981) noted this distinction, and conducted a major field study investigating race main effects and the interaction between raters and ratees.…”
mentioning
confidence: 99%